68Ga-PSMA PET/MR Showing Intense PSMA Uptake in Nodular Fasciitis Mimicking Prostate Cancer Metastasis. (October 2016) - Henninger, Martin; Maurer, Tobias; Hacker, Charlotte; Eiber, Matthias
Abstract : Abstract: The recently introduced PSMA PET has developed as a powerful imaging tool for staging of prostate cancer. This case showed an intense uptake of 68 Ga-PSMA in a soft-tissue mass of the rectus femoris muscle. Histopathology revealed the diagnosis of fasciitis nodularis. Therefore, it advises caution particularly in patients with solitary and atypical located lesions as they might not be indicative for metastatic prostate cancer, but eventually be caused by different conditions.